How quality, service, and marketing drive customer satisfaction in medium-scale manufacturing companies - Rukhmana, Ulfa; Dwiarta, I Made Bagus (Manajemen dan Bisnis, 2026)
This study aims to examine the influence of product quality, after-sales service, and marketing communications on customer satisfaction in a medium-scale manufacturing industry in Indonesia. An exploratory quantitative approach was applied using survey data collected from 120 customers of Adisa Jaya Industri, a metal-milling machine manufacturer in Gresik. The data were analyzed using SEM-AMOS. The results indicate that product quality, after-sales service, and marketing communications each have a positive and significant influence on customer satisfaction. Improved machine reliability, service responsiveness, and consistent digital communications strengthen customer trust and loyalty. These findings confirm that satisfaction in the manufacturing sector depends not only on product excellence but also on the effectiveness of technical support and communication strategies, in the context of B2B manufacturing—an area that remains underexplored in previous research. These findings provide managerial insights for manufacturing companies to enhance competitiveness through sustainable integrated quality management, strengthened after-sales services, and consistent digitalization of marketing communications. This study provides empirical evidence that customer satisfaction in the manufacturing industry is not only determined by product quality, but is also influenced by after-sales service and effective marketing communications, especially in medium-scale manufacturing companies